CYP2B6 Genetic Polymorphisms, Depression, and Viral Suppression in Adults Living with HIV Initiating Efavirenz-Containing Antiretroviral Therapy Regimens in Uganda: Pooled Analysis of Two Prospective Studies - Chang, Jonathan L. (AIDS Res Hum Retroviruses, 2018)
Single-nucleotide polymorphisms (SNPs) in CYP2B6 have been shown to predict variation in plasma efavirenz concentrations, but associations between these SNPs and efavirenz-mediated depression and viral suppression are less well described. We evaluated three SNPs in CYP2B6 (rs3745274, rs28399499, and rs4803419) in Ugandan persons living with HIV. To define exposure, we used previously published pharmacokinetic modeling data to categorize participants as normal, intermediate, and poor efavirenz metabolizers. Our outcomes were probable depression in the first 2 years after antiretroviral therapy (ART) initiation (mean score of >1.75 on the Hopkins Symptom Depression Checklist) and viral suppression 6 months after ART initiation. We fit generalized estimating equation and modified Poisson regression models adjusted for demographic, clinical, and psychosocial characteristics with or without individuals with depression at the time of ART initiation. Among 242 participants, there were no differences in the pre-ART depression or viral load by efavirenz metabolism strata (p > .05). Participants were classified as normal (32%), intermediate (50%), and poor (18%) metabolizers. Seven percent (56/242) of follow-up visits met criteria for depression. Eighty-five percent (167/202) of participants who completed a 6-month visit achieved viral suppression. CYP2B6 metabolizer strata did not have a statistically significant association with either depression [adjusted risk ratio (aRR) comparing intermediate or poor vs. normal, 1.46; 95% confidence interval (CI), 0.72–2.95] or 6-month viral suppression (aRR, 1.01; 95% CI, 0.88–1.15). However, in analyses restricted to participants without pre-ART depression, poorer CYP2B6 metabolism was associated with increased odds of depression (adjusted odds ratio, 4.11; 95% CI, 1.04–16.20). Efavirenz-metabolizing allele patterns are strongly associated with risk of incident depression. Future work should elucidate further region-specific gene–environment interactions and whether alternate polymorphisms may be associated with efavirenz metabolism.